2022
DOI: 10.1021/acsanm.2c00233
|View full text |Cite
|
Sign up to set email alerts
|

MoSe2/SnS Nanoheterostructures for Water Splitting

Abstract: We show that the colloidal growth of SnS nanosheets (NS), a group IV metal chalcogenide (MC), on MoSe2 NS, a transition metal dichalcogenide (TMDC), results in the formation of type-II nanoheterostructures (NHS). The MoSe2/SnS NHS synthesis is accompanied by in situ generation of MoO3–x at the MoSe2 and SnS interface activating the otherwise electrochemically inert basal planes of MoSe2 NS. The MoSe2/SnS NHS exhibit more active sites, and the built-in electric field at the interface enhances the rate of charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…These reports suggest that a secondary material is required in order to expose the edges and make full utilisation of these MoX 2 compounds. Similarly, Singh et al 182 reported the improved performance of the MoSe 2 /SnS nanocomposite for water splitting.…”
Section: Materials Advances Reviewmentioning
confidence: 87%
“…These reports suggest that a secondary material is required in order to expose the edges and make full utilisation of these MoX 2 compounds. Similarly, Singh et al 182 reported the improved performance of the MoSe 2 /SnS nanocomposite for water splitting.…”
Section: Materials Advances Reviewmentioning
confidence: 87%
“…116 Therefore, exploiting efficient and durable bifunctional electrocatalysts to reduce energy consumption toward HER and OER processes is urgent. 117,118 However, it is limited by the incompatibility between HER and OER catalytic Li−S batteries employing metal Li and sulfur as electrode active materials are promising candidates for next-generation energy storage systems due to the high theoretical capacity (1675 mA h g −1 ) and extraordinary energy density (2600 W h kg −1 ). 121−123 The high specific energy is ascribed to sulfurrelated redox reactions: phase transformations from solid to liquid (S 8 → Li 2 S 8 → Li 2 S 6 → Li 2 S 4 ) and from liquid to solid (Li 2 S 4 → Li 2 S 2 → Li 2 S).…”
Section: Bief In Electrocatalysismentioning
confidence: 99%
“…Apart from OER, the HER process is also important for water splitting . Therefore, exploiting efficient and durable bifunctional electrocatalysts to reduce energy consumption toward HER and OER processes is urgent. , However, it is limited by the incompatibility between HER and OER catalytic sites. The 2D ternary nickel thiophosphate (NiPS 3 ) nanosheet exposed with (001) facets is an ideal OER electrocatalyst, and the epitaxial in-growth NiPS 3 /Ni 2 P interface shows the lowest absolute value of Δ G H* for HER.…”
Section: Bief In Electrocatalysismentioning
confidence: 99%
“…35,36 Besides, abundant active edge sites with desirable electronic structures can be provided for altering the reaction mechanisms. 37,38 On further combination with the excellent stability contributed by the robust interface, signicantly reinforced electrochemical performances have been achieved by EHs, outperforming their building blocks with single components. 39,40 As an emerging but fast-rising eld, numerous breakthroughs have been witnessed in recent years, while a dedicated review is still lacking.…”
Section: Introductionmentioning
confidence: 99%